2014
DOI: 10.1063/1.4896058
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation and recombination of D2 on Cu(111): Ab initio molecular dynamics calculations and improved analysis of desorption experiments

Abstract: Obtaining quantitative agreement between theory and experiment for dissociative adsorption of hydrogen on and associative desorption of hydrogen from Cu(111) remains challenging. Particularly troubling is the fact that theory gives values for the high energy limit to the dissociative adsorption probability that is as much as two times larger than experiment. In the present work we approach this discrepancy in three ways. First, we carry out a new analysis of the raw experimental data for D2 associatively desor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
210
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(221 citation statements)
references
References 93 publications
10
210
1
Order By: Relevance
“…Finally, note that the experimental value for D 2 /Cu(111) was originally reported to be χ v 0.54, 67 but this was based on a different definition of the vibrational efficacy, in which different values for P r,0 are used for v = 0 and 1. In figure 6 the reaction probability for (v = 0, J = 0, 2, 4, 6, 8) D 2 dissociating on Cu(111)is shown for both tested functionals, also comparing to the reaction probability curves extracted from experiments 81. The analysis of the experimental results showed that reaction first decreases with J, up to about J = 4, and then increases with J 67,81.…”
mentioning
confidence: 89%
“…Finally, note that the experimental value for D 2 /Cu(111) was originally reported to be χ v 0.54, 67 but this was based on a different definition of the vibrational efficacy, in which different values for P r,0 are used for v = 0 and 1. In figure 6 the reaction probability for (v = 0, J = 0, 2, 4, 6, 8) D 2 dissociating on Cu(111)is shown for both tested functionals, also comparing to the reaction probability curves extracted from experiments 81. The analysis of the experimental results showed that reaction first decreases with J, up to about J = 4, and then increases with J 67,81.…”
mentioning
confidence: 89%
“…On the one hand, the AIMD method has already been found [62,96] to underestimate the experimental surface temperature dependence of the dissociation probability of D 2 on Cu(111) [97]. On the other hand, the extent to which surface temperature enhances reactivity has been experimentally observed to decrease with increasing collision energy [9,50,51], and Schoofs et al [92] even reported that no dependence of the sticking probability on T s was observed (within their experimental sensitivity [98]) at E i ≈ 0.7 eV (about 0.3 eV lower than the collision energy that we have simulated).…”
Section: Surface Temperature Dependence Of Smentioning
confidence: 99%
“…These full-dimensional calculations were used to test some of the approximations made in reduced-dimensionality calculations (139). They have been used to model H 2 on copper (22,140) and CHD 3 on Pt(111) (141-143) and on Ni(111) (139,144), but extension to CH 4 is difficult due to artificial IVR that can occur between bonds of the same frequency in classical calculations.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than using a quantum approach to propagate the dynamics, Kroes and coworkers (22,(139)(140)(141)(142)(143)(144) use quasi-classical trajectory calculations in their ab initio molecular dynamics (AIMD) simulations of gas-surface reactions. One advantage of the AIMD treatment is that it includes all molecular degrees of freedom as well as the surface-atom motion, which is not yet possible using quantum dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation